VDS info and support service: The analysis of the service’s work in 2012 - Radovanović Una; Popović Milica (Temida, 2014)
VDS info and victim support service was established as part of the Victimology Society of Serbia in 2003, and its focus is on providing support and assistance to victims of various forms of crime. It is also the only service of general type in Serbia, which provides assistance and support to victims of crime, regardless of gender, age, form of victimization or any other personal characteristics. The aim of this paper is to analyze the work of VDS info and victim support service in the 2012, with special emphasis on ways of providing assistance and support to people who have contacted the Service because of workplace and domestic violence, as well as convicts, considering that those are also the most common causes for contacting the Service.